The respiratory analeptic action of isoprenaline and orciprenaline (Revista Española de Fisiología, 1971)
The respiratory analeptic action of isoprenaline and orciprenaline has been de monstrated. The results show that orciprenaline has larger respiratory analeptic action than isoprenaline.We combined them with differents drugs trying to find their mechanism. In this way we did five groups of dogs. The first one was the control with continued infusion of these simpathomimetics amines.The other groups were done blocking differents levels with the administration of bicarbonate, INPEA, protoveratrine and reserpine respectively.The bicarbonate reduces the frequency of respiration. Protoveratrine and INPEA reduces the amplitude of respiration.Reserpine does not potentiate the respiratory analeptic action of these /3-simpatho- mimetics amines. This case is the first one in wich reserpine does not potentiate one simpathomimetic action.We think that analeptic action of orciprenaline is for direct action on respiratory centers, not a simpathomimetics action. We don’t think so about isoprenaline.